Effects on size, optical and antibacterial activity of pristine and Cr-doped NiO prepared by microwave-assisted method. (2022) - Nallathambi, A.; Prakasam, A.; Azhagu Raj, R.; Anbarasan, P.M.; Ragupathi, C.
Abstract: In this work pristine and Cr-doped NiO were synthesized by microwave-assisted method. The products were characterized by X-ray diffraction (XRD), UV–vis absorption spectroscopy and photoluminescence (PL) spectroscopy. The significant feature of this manuscript is that the effects of pristine and Cr-doped NiO on the structural and optical properties of Cr-doped NiO were investigated for the first time. The average particle size of different samples was below 24 to13 nm. Pristine and Cr-doped NiO antibacterial activity is shown by all the prepared samples.